Penerapan Kaidah Nahyu Pada Juz 30: (Analisis Muhammad Khalid al-Sabt) - Saepudin, Dindin Moh (MAGHZA: Jurnal Ilmu Al-Qur’an dan Tafsir, 2019)
The Uá¹£Å«l scholars in both jurisprudence and interpretations of al-Nahyu mean al-TahrÄ«m (Ø§Ù„ØªØØ±ÙŠÙ…) or MajazÄ«, which has several meanings such as duÄ (Ø§Ù„Ø¯Ø¹Ø§Ø¡), iltimas (Ø§Ù„ØªÙ…Ø³), irsyÄd (Ø§Ø±Ø´Ø§Ø¯), dawÄm (Ø¯ÙˆØ§Ù…), bayÄn al-'aqÄ«bah (Ø¨ÙŠØ§Ù† Ø§Ù„Ø¹Ù‚ÙŠØ¨Ù‡), al-yais (Ø§Ù„ÙŠØ£Ø³), parknÄ« (Ø§Ù„ØªÙ…Ù†ÙŠ), tahdÄ«d, (ØªÙ‡Ø¯ÙŠØ¯), karÄhah (Ø§Ù„Ù’ÙƒÙŽØ±ÙŽØ§Ù‡Ø©ÙŽ), taá¸¥qir (ØªØÙ‚ÙŠØ±), i'tinØ§Ä) and taubÄ«kh (ØªÙˆØ¨ÙŠØ®). The use of nahyu is more emphasized in Islamic law and operational law. Whereas the practice of nihilism on matters of faith, faith and morals are still rare. Therefore, the author can analyze la nahyu with the approach of Muhammad Khalid al-Sabt in QawÄ'id al-TafsÄ«r's work on Juz 30 which is a Makiyyah letter and is repeated 4 times in al-á¸ŒuhÄ's letter: 9.10, al-'Alaq: 19, al-MÄ'un: 3. Besides, the research shows that Usman bin Sabith's use of the Rash law is the first rule used in 3 verses, the fourth rule in 1 verse. Whereas the meaning of nahyu means 3 times the meaning of al-tahrÄ«m. The meaning of majazÄ« is repeated 1 time with the meaning of bayÄn al-'aqÄ«bah 1 time. It shows that the verses of Makiyyah do not offend Islamic law but emphasize universal faith, creed, and morals.